REFORMULASI KEDUDUKAN ORGANISASI PROFESI PERSATUAN DOKTER GIGI INDONESIA DENGAN BERLAKUNYA UNDANG-UNDANG NOMOR 17 TAHUN 2023 TENTANG KESEHATAN - Hoediono, Charissa Roderica; Pramono, Budi; Sulaksono, Sulaksono (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study analyzed the Reformulation of the Legal Status of the Indonesian Dentist Association Professional Organization with the Enactment of Law Number 17 of 2023 concerning Health. The existence of Law Number 17 of 2023 concerning Health has significant implications for the legal status of professional organizations, including the Indonesian Dentist Association (PDGI). Before the enactment of this law, PDGI as a professional organization had a strong position in regulating and supervising dental practices in Indonesia. However, with the enactment of the new Health Law, there has been a change in the governance of the medical profession which has a direct impact on the legal status of PDGI. With the enactment of Law Number 17 of 2023 concerning Health, the absence of various roles and functions of professional organizations that were previously contained in laws and regulations. In the future, the various roles of these health professional organizations will be carried out by the government, or institutions under the authority of the government. Therefore, this study is juridical-normative research using statute, conceptual and comparative approaches.